Persepsi Kemudahan Penggunaan Canva Dalam Mendesain Presentasi Bagi Guru SMKN 1 Kuala Mandor B - Mardani, Wina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Canva, as a graphic design application, is beneficial for learning, allowing teachers to design teaching material presentations by utilizing various features, assets, and elements available within the platform. With its diverse design options, Canva enables teachers to create engaging and interactive presentations, making the learning process less monotonous. This study aims to explore teachers' perceptions of the ease of using Canva as a tool for designing teaching material presentations. The researcher employed a descriptive survey method with a quantitative approach. The instrument used was a questionnaire with a Likert scale of 1-4, distributed to 23 subject teachers at SMKN 1 Kuala Mandor B who had used Canva to design their teaching material presentations. The collected data were then analyzed to provide an overall picture of the teachers' perceptions. The results showed that all respondents agreed that Canva is easily accessible, allowing every teacher to take advantage of it in designing their presentations. 70% of the teachers reported being proficient and comfortable using Canva"™s various features for designing teaching materials, while 30% reported not being proficient, indicating that Canva has not fully met teachers' expectations in this area. The researcher suggests efforts to improve teachers' abilities in utilizing Canva through comprehensive training to optimally design more engaging presentations that meet current student needs.